PERANCANGAN DAN PEMBUATAN APLIKASI TRACKING OBJECT PADA VIDEO DENGAN METODE KERNEL - BASED - Wilson -; Liliana -; Kartika Gunadi (Jurnal Infra, 2013)
Utilization as a surveillance camera (CCTV) still has many weaknesses. The camera just record it, so it still takes control of guard constantly. With these limitations it needed an additional capability to boost surveillance cameras work. One of the additional capabilities that can be used is the motion detection which helps signal the event of unusual movements were caught on camera.Detection of object motion can be used to capture movements recorded from a CCTV. Detection process starts by reading each video frame, from frame - frame segmentation process will be carried out so that objects that are obtained from the video. After that, the object - the object stored will be processed using the kernel method - based on detecting movement going from object - the object.The end result is a software application that can signal the moving objects from the video. The software was tested with some video with different conditions - different. If the object in the video is too big or too small tracking process will be inaccurate.